Gênero e sexualidade na escola pública: como os alunos e os professores de Biologia da EA-UFPA observam o papel da escola na orientação sexual - OLIVEIRA, Alexandre Macedo (2019)
Sexuality is currently considered an inherent attribute of the human being, especially among adolescent girls of reproductive age where the incidence of unwanted pregnancies and sexually transmitted infections (STIs) is alarming. With the advent of Law no. 60/2009, which establishes sex education in high school establishments, it became intentional to investigate and analyze gender / sexuality relations in school. In this quantitative-qualitative case study we aimed to know and analyze the perception of Biology teachers and adolescents in gender / sexuality relations in public school of Application of UFPA in the city of Belém - PA. For that, we conducted structured interviews with biology teachers and students of the 2nd year of high school, as well as observations of the routine of the youngsters and teachers in the classroom in order to understand how gender / sexuality relationships occur on a daily basis -day of young people and, as teachers and students think about human sexuality. The results highlight the insecurity and lack of knowledge on the part of Biology students and educators regarding the concepts of themes related to sexuality, as well as the feasibility of the elaboration of a program of sexual orientation in the school that incorporates the debate on sexuality / gender issues , making critical readings of textbooks, reflecting on school practice from a gender perspective, developing works that address sexuality, or debating on literatures that approach the theme, collaborating with educators in their role as a training element for young people in the construction of their conceptions and information necessary for the development of their sexuality.